The last missing species born of a confusing puzzle: Leopoldia nigdeensis (Asparagaceae, Scilloideae), a new species from Türkiye - Eker, İsmai̇l; Eroğlu, Hüseyi̇n (Phytotaxa, 2024)
The concept of Muscari massayanum (=Leopoldia massayana), previously treated by Davis & Stuart in the Flora of Turkey, was found to be a mixed species assemblage and included the species Muscari erdalii (=Leopoldia erdalii) and Muscari erzincanicum (=Leopoldia erzincanica), which arose from this confusion. However, in the latest evaluations by the authors of this article, the last missing piece of the confusing puzzle has been put forward in this study. Thus, a new species Leopoldia nigdeensis from Anatolia is described in this study. The new species is morphologically partly similar to Leopoldia massayana, L. erzincanica, L. oztasii, L. tenuiflora and L. erdalii, but differs from all of them with clear features in flower, fruit and seed characteristics.